Influence of the Manganese Substitution on the Cation Distribution and Magnetic Structure of the Spinel-Related Life1-XMn1+XO4 (X=0.00, 0.25, 0.50, 0.75) System - Gautier-Zamora, J; Gautier-Zamora, J (SPRINGER INTERNATIONAL PUBLISHING AG, 2019)
We report a modified synthesis for lithium manganese ferrites LiFe1-xMn1+xO4 (x=0.00, 0.25, 0.50, 0.75) based on the thermal decomposition of nitrates which produces purer materials when compared to other synthesis methods. The different oxidation states of the various cations and their preferences for particular crystal sites within the spinel-related structure lead to a complex cation distribution and magnetic properties which depend strongly on the composition. The large, almost complete, lithium occupancy of the tetrahedral sites in the spinel structure for particular compositions and the concomitant occurrence of unusual oxidation states of iron show how the synthesis method can be tailored to obtain materials which can have promising applications in the field of lithium-containing batteries.